1967
DOI: 10.1002/art.1780100604
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related antinuclear factors: Immunologic characteristics and associated clinical aspects

Abstract: A nuclear factors has been reported in association with age. Seligmann found that 16 per cent of sera from healthy persons 60 to 80 years old demonstrated nuclear reactivity.% Litwin and Singer found antinuclear factors present in approximately 7 per cent of non-rheumatic individuals and in none of the younger control individuak2 An increased occurrence of antinuclear factors was also noted by Cammarata et al. among an aged group which, however, included occasional patients with rheumatoid arthriti~.~ It has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
1

Year Published

1971
1971
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 23 publications
3
11
0
1
Order By: Relevance
“…Such an association has been reported by Moskowitz and Katz (7), but in their patients, the predominant symptomatology was related to the basic rheumatoid disease rather than to the chondrocalcinosis. The presence of a transiently positive antinuclear factor in our patient lends some support to the possibility of underlying connective tissue disease; however, it is known that up to 207& of healthy women over the age of 60 may have positive tests for antinuclear factor (8). The cystic erosions as seen in the wrists and shoulders, while suggestive of rheumatoid arthritis, have also been reported to occur in both idiopathic chondrocalcinosis and chondrocalcinosis associated with hemochromatosis (9).…”
Section: Electron Microscopy and Electron Diffraction Studiessupporting
confidence: 60%
“…Such an association has been reported by Moskowitz and Katz (7), but in their patients, the predominant symptomatology was related to the basic rheumatoid disease rather than to the chondrocalcinosis. The presence of a transiently positive antinuclear factor in our patient lends some support to the possibility of underlying connective tissue disease; however, it is known that up to 207& of healthy women over the age of 60 may have positive tests for antinuclear factor (8). The cystic erosions as seen in the wrists and shoulders, while suggestive of rheumatoid arthritis, have also been reported to occur in both idiopathic chondrocalcinosis and chondrocalcinosis associated with hemochromatosis (9).…”
Section: Electron Microscopy and Electron Diffraction Studiessupporting
confidence: 60%
“…The incidence of IgG, IgM, and IgA * ANF in OA sera correspond closely to that of age and sex matched controls. Earlier data indicate that ANF -* occurs with increasing frequency in older persons, 64 >64 expecially women (Svec and Veit, 1967;Willkens, Whitaker, Anderson, and Berven, 1967). Accorpolymorphonu-dingly the rather high prevalence of ANF in the kG GS-ANF in controls and the OA patients can probably be asfindings in one cribed to their age and sex.…”
Section: Resultsmentioning
confidence: 87%
“…An increased occurrence of such factors with advancing age has been noted as well (7). Unfortunately, despite the reliance often placed on the fluorescent antinuclear antibody test, statistical analysis has demonstrated that a correct interpretation of this test often depends upon the overall clinical picture of each patient (8).…”
Section: Brief Report Secondary Syphilis Mimicking Systemic Lupus Erymentioning
confidence: 99%